Violin Secrets: 101 Strategies for the Advanced Violinist - Nardolillo, Jo (Rowman & Littlefield Publishers, 2015)
In Violin Secrets: 101 Performance Strategies for the Advanced Violinist, author and violinist Jo Nardolillo surveys the cutting edge of current violin technique, combining tradition and innovation in one volume. Blending traditional strategies that have produced generations of legendary performers with modern ideas, Nardolillo reveals the secrets of today’s most sought-after master teachers, garnered through her decade of study at top conservatories across the nation. With more than a quarter century of experience teaching at the advanced level, she has refined and distilled these essential concepts into clear, concise, step-by-step instructions, complete with original illustrations and helpful tips. Violin Secrets is an indispensable resource for any and all serious violinists. The first chapter tackles the toughest challenge on the wish list of every established professional, dedicated student, and passionate amateur: understanding why immaculate intonation is so difficult (and exploring ways to achieve it). Further chapters address the advanced techniques of fingerboard mapping, mastering spiccato, controlling vibrato, playing into the curve, small-hand technique, and navigating comfortably in high positions. An extensive section on practice strategies blends concepts from learning theory, sports psychology, and Zen, and the chapter on artistry offers insight on creating expressive phrases, connecting with the audience, and developing a unique artistic voice. Violin Secrets examines overcoming performance anxiety, choosing the right music editions, being a strong section player in an orchestra, leading productive chamber music rehearsals, and winning auditions. Violin Secrets is beautifully illustrated with original drawings by T. M. Larsen, musical examples from the standard literature, and a violinist’s family tree that traces these secrets back through to the founding fathers of violin technique.The Music Secrets for the Advanced Musician series is designed for instrumentalists, singers, conductors, composers, and other instructors and professionals seeking a quick set of pointers to improve their work as performers and producers of music. Easy to use and intended for the advanced musician, contributions to Music Secrets fill a niche for those who have moved beyond what beginners and intermediate practitioners need.